Satisfaction and Quality of Life in Patients with Dental Implants - De Romero, Beatriz Cepeda; Pineda, Cristhian Santiago Acuña; Castaño, Andrés Felipe Quintero (British Journal of Healthcare and Medical Research, 2025)
Satisfaction and quality of life are important factors in assessing the outcome of dental therapy. Method: Minimal risk, retrospective, years 2022 -2023. Sample 36 patients with the use of dental implants contacted by telephone, voluntary participation and signing of the informed consent. Variables studied: demographic data of each patient, assessing the degree of satisfaction with implant placement in the preoperative, postoperative and rehabilitation phases by means of a survey (OIIP -15 questions) on a Likert scale from 1 to 5: 1 very satisfied, 2. satisfied, 3. partially satisfied 4. Dissatisfied and 5 very dissatisfied. Quality of life assessment by survey (OHIP-14 questions): 1. Never, 2. Rarely, 3. Sometimes, 4. Repeatedly, 5. Always. Descriptive statistics with absolute and relative frequencies; inferential statistics using medians and interquartile range with Fisher’s test and chi-square. Results: Mean age 65.8 ± 9.7 years, Healthy (ASAI) (55.6%). Patients very satisfied (75-100%) with dental implant treatment (OIIP-15) and never presented an alteration in their quality of life (OHIP-14) during the two years of study, both in terms of functionality and socialization (61.1%-100%). The rehabilitation of the patients, with significant difference Hybrid Prosthesis (p=0.039.), overdenture (p=0,046), single crowns (p=0.011), fixed prosthesis (P=0,003). Conclusion: Adults of legal age, healthy or with controlled systemic diseases, are satisfied with the use of dental implants during two years of use and have a good quality of life.